Embryology and Morphological (Mal)Development of UPJ - Avanoglu, Ali; Tiryaki, Sibel (Frontiers in Pediatrics, 2020)
Kidney parenchyma and collecting system arise from two different embryologic units as a result of a close interaction between them. Therefore, their congenital abnormalities are classified together under the same heading named CAKUT (congenital abnormalities of the kidney and urinary tract). The pathogenesis of CAKUT is thought to be multifactorial. Ureteropelvic junction obstruction (UPJO) is the most common and most investigated form of CAKUT. Despite years of experimental and clinical research, and the information gained on the embryogenesis of the kidney; its etiopathogenesis is still unclear. It involves both genetic and environmental factors. Failure in the development of the renal pelvis, failure in the recanalization of the ureteropelvic junction, abnormal pyeloureteral innervation, and impaired smooth muscle differentiation are the main proposed mechanisms for the occurrence of UPJO. There are also single-gene mutations like AGTR2, BMP4, Id2 proposed in the etiopathogenesis of UPJO.